Toward High Efficiency Polymer Solar Cells: Influence of Local Chemical Environment and Morphology. Issue 1 (22nd September 2016) - Zhou, Cheng; Zhang, Guichuan; Zhong, Chengmei; Jia, Xiaoe; Luo, Peng; Xu, Rongguo; Gao, Ke; Jiang, Xiaofang; Liu, Feng; Russell, Thomas P.; Huang, Fei; Cao, Yong
Abstract : The chemical structure of conjugated polymers plays an important role in determining their physical properties that, in turn, dictates their performance in photovoltaic devices. 5‐Fluoro‐2, 1, 3‐benzothiadiazole, an asymmetric unit, is incorporated into a thiophene‐based polymer backbone to generate a hole conducting polymers with controlled regioregularity. A high dipole moment is seen in regioregular polymers, which have a tighter interchain stacking that promotes the formation of a morphology in bulk heterojunction blends with improved power conversion efficiencies. Aliphatic side chain substitution is systematically varied to understand the influence of side chain length and symmetry on the morphology and resultant performance. This side chain modification is found to influence crystal orientation and the phase separated morphology. Using the asymmetric side chain substitution with regioregularity of the main chain, an optimized power conversion efficiency of 9.06% is achieved, with an open circuit voltage of 0.72 V, a short circuit current of 19.63 mA cm −2, and a fill factor over 65%. These results demonstrate that the local chemical environment can dramatically influence the physical properties of the resultant material. Abstract : The unidirectional regioregular conjugated polymers using 5‐fluoro‐2, 1, 3‐benzothiadiazole (FBT) asymmetric unit were synthesized. Compared with the regiorandom control polymers, the regioregular polymers with a unidirectional fluorine atom alignment can lead to a progressive dipole moment along the backbone. The regioregular FBT polymers exhibit tighter interchain stacking and better morphology in bulk heterojunction blends, giving rise to improved power conversion efficiency.